Supporting our supervisors: a Summary and Discussion of the Special Issue on CBT supervision. (14th October 2016) - Newman, Cory F.; Reiser, Robert P.; Milne, Derek L.
Abstract: Contributors to this Special Issue of the Cognitive Behaviour Therapist have considered the kind of infrastructure that should be in place to best support and guide CBT supervisors, providing practical advice and extensive procedural guidance. Here we briefly summarize and discuss in turn the 10 papers within this Special Issue, including suggestions for further enhancements. The first paper, by Milne and Reiser, conceptualized this infrastructure in terms of an 'SOS' (supporting our supervisors) framework, from identifying supervision competencies, to training, evaluation and feedback strategies. The next nine papers illustrate this framework with specific technical innovations, educational enhancements and procedural issues, or through comprehensive quality improvement systems, all designed to support supervisors. These papers suggest an assortment of workable infrastructure developments: two large-scale and comprehensive initiatives, some promising proposals and technologies, and a series of local, exploratory work. Collectively, they provide us with models for further developing evidence-based cognitive-behavioural supervision, and offer practical suggestions for giving supervisors the tools and support to maximize their supervisees' learning, and to improve the associated client outcomes. Much research and development work remains to be done, and successful implementation will require institutional and political support, as well as cross-cultural adaptations. We conclude with an optimistic assessment of progress toward addressing some of the infrastructure improvements required to adequately support supervisors.